Survival outcomes of neoadjuvant chemoradiation followed by surgery versus definitive chemoradiation in ESCC: real-world data - Alhalabi, Ahmad; Abdo, Theresa; Sabbagh, Saad; Herrán, María; Sarna, Kaylee; Tfayli, Rami; Nahleh, Zeina; Nagarajan, Arun (Frontiers in Oncology, 2025)
BackgroundEsophageal squamous cell carcinoma (ESCC) is an aggressive malignancy that has poor survival. Management of ESCC depends on the resectability of the disease, certain patient characteristics, fitness for surgery, and the anatomic complexity of the disease location. Treatment options include either Neoadjuvant chemoradiotherapy (NCR) followed by surgery or definitive Chemoradiation (DCR). While randomized trials have provided insights into both strategies, no large-scale retrospective real-world studies have been conducted to compare these approaches in diverse, unselected populations. This study assesses real-world outcomes of NCR versus DCR using the National Cancer Database (NCDB).MethodsA retrospective cohort study was conducted using data from the NCDB, focusing on patients with ESCC from 2004 to 2020. Propensity score matching (PSM) (1:1) was utilized. Univariate and multivariate Cox regression analyses were employed.ResultsN = 386 patients with esophageal cancer, with a median age of 64 years (IQR, 57.0-70.0), were identified. Patients were evenly distributed between the DCR and NCR groups, with a total of N = 193 participants. We further selected patients with ESCC, a total of N = 311 patients. NCR demonstrated a significantly extended overall survival (OS) compared to those who received DCR, with a median of 33.15 months vs. 20.5 months (P-value: 0.0069), respectively. Patients receiving DCR had significantly worse OS compared to patients receiving NCR with HR 1.38, 95% CI 1.05–1.81, p=0.0206. Patients with tumors in the thoracic esophagus (C15.3) showed significant survival benefit from surgery (p=0.0070), whereas no benefit was seen for cervical tumors (C15.0), likely due to anatomical complexity and limited sample size.ConclusionNCR followed by surgery, when feasible, offers survival benefits for patients with ESCC, especially for locally advanced tumors in the thoracic esophagus.